Correctness of use of microdosed combination oral contraceptives in young women - N A Buralkina (IP Berlin A.V., 2017)
The article describes the effective use of a microdosed combined oral contraceptive containing drospirenone in young women. The use of synthetic progestin IV generation due to antiandrogenic and unique antimineralocorticoid effects makes it possible to obtain an additional spectrum of medicinal properties, has a high contraceptive effectiveness, is well tolerated, reduces the symptoms of premenstrual syndrome, acne, and seborrhea with virtually no effect on body weight in young women.